71.4k views
2 votes
Factorise fully 2x^2-8x

User Prototik
by
5.0k points

2 Answers

3 votes

Answer:

2x(x-4)

Explanation:

2
x^(2)-8x= 2(
x^(2)-4x)= 2x(x-4)

User Lemuel
by
5.7k points
3 votes

Answer:


\mathrm{Factor}\:2x^2-8x:\:2x\left(x-4\right)

Explanation:

Given the expression


2x^2-8x


\mathrm{Apply\:exponent\:rule}:\quad \:a^(b+c)=a^ba^c


x^2=xx

so the expression becomes


2x^2-8x=2xx-8x


=2xx-2\cdot \:4x


=2x\left(x-4\right)
\mathrm{Factor\:out\:common\:term\:}2x

Therefore,


\mathrm{Factor}\:2x^2-8x:\:2x\left(x-4\right)

User Prilaga
by
5.1k points